Protection and Legal Aid for Women Migrant Workers with Problems in Kuala Lumpur Malaysia - Sundary, Rini Irianti; Sambas, Nandang; Setiadi, Edi (UPT Publikasi Ilmiah UNISBA, 2025)
Indonesia is one of the largest migrant worker-sending countries in Southeast Asia, with Malaysia being a major destination. Most of these migrant workers are women working in the informal sector, such as domestic helpers, who are often vulnerable to exploitation and human rights violations. The research on the protection of Indonesian female migrant workers in Malaysia aims to identify the problems faced, analyze the effectiveness of existing policies and programs, and provide recommendations to improve their protection and welfare. This research is important to contribute to improving the system of placement and protection of migrant workers, and to ensure that their rights are respected and protected. The research method used is the normative juristic method, which prioritizes secondary data, but is also complemented by primary data in the form of interviews and discussions with migrant workers who are experiencing legal problems in Kuala Lumpur Malaysia. In conclusion, female migrant workers, especially those working in the informal sector as domestic workers, are highly vulnerable to various forms of human rights violations, including exploitation, physical and psychological violence, sexual harassment, excessive working hours, inadequate wages, and poor working conditions. Illegal status exacerbates vulnerability, as illegal migrant workers do not have the same legal protections as legal migrant workers and are afraid to report abuses they experience